A STUDY ON THE CHARACTER JANE EYRE IN THE NOVEL “JANE EYRE” BY CHARLOTTE BRONTË = NGHIÊN CỨU VỀ NHÂN VẬT JANE EYRE TRONG TIỂU THUYẾT “JANE EYRE” CỦA CHARLOTTE BRONTË - Hoàng, Thị Mai Hồng (2020)
The whole graduation paper consists of three chapters (chapter 1, chapter 2 and chapter 3). In the introduction, I represented the ground for my choosing the thesis, the aim of the study and the structure of the graduation paper. Chapter 1, Literature review, gives the brief outline of some theoretical background. The literary background deals with the most general concepts of “fiction”, “character” and “critical realism”. This chapter also gives an introduction to England in mid-nineteenth century with historical background and the women in Victorian Era. All of these serve for a further understanding of the main thesis. Chapter 2 deals with Charlotte Brontë’s life and her literary works. It is followed by the making, the summary of the novel and the female protagonist in this novel. Chapter 3, the main chapter, focuses on presenting and analyzing the character Jane Eyre with her striking characteristics: Strong and determined, kind-hearted and tolerant, passionate and sincere love for her boss – Mr. Rochester. Moreover, this chapter also presented Charlotte Brontë’ s challenges to the conceptions of appropriate female behaviors in the 19th century in terms of femininity and rebellion, talents, passion. Some remarks on Charlotte Brontë’s writing style help to understand her artistic style displayed in “Jane Eyre”, apart from the influence of Victorian literature and her family on her writing.